Análise experimental de armadura interna para cisalhamento em vigas de concreto armado - ABRANTES, Jedson Henryque Corrêa (2021)
The improvement of constructive techniques has allowed a practical execution combined with the safety, comfort and durability of structures. Thus, in order to prevent sudden and fragile ruptures and maintain structural functionality, research on new forms of shear reinforcement has taken place in order to connect resistance, efficiency and durability of structures. In this scenario, this study seeks to present an analysis of the behavior of unconnected shear reinforcement known as W stirrups and headed shear reinforcement assemblies in reinforced concrete beams, comparing those with the results obtained from the closed stirrups. In order to do this, 5 wide beams (500 x 210 x 2050 mm) were tested; 1 reference beam without shear reinforcement, 1 closed stirrup, 1 headed shear reinforcement and 2 wide beams with W stirrups, with and without hooks against delaminaton. The experimental program presents as main variables the type of shear reinforcement and the type of anchorage, which can be external and internal. Results of vertical displacement, strains on surface of the concrete, flexural reinforcement and shear reinforcement, crack pattern, rupture load and failure modes are presented. The results obtained indicate that W stirrups wide beams, specifically with hooks, presented a gain of 36.54% of load capacity in comparison to the reference beam, and a considerable increase in stiffness performance regarding the displacement values, the strain on the shear reinforcement and the strain on the concrete surface. All the wide beams presented similar behavior related to the strain on the flexural reinforcement, whereas they showed different behavior when compared to each other considering the strains on the concrete surface. The stiffer behavior was noticed in headed shear reinforcement wide beams (S-3.5-0.16). With regard to the strains on shear reinforcement, the W stirrup presented less strains levels at the same loading in relation to other beams and the conventional stirrup showed greater strain levels, especially when compared to the steel bars located next to the wide beam loading point.